Aplikasi kombinasi penggunaan POC ikan lemuru dan pupuk anorganik NPK pada budidaya tanaman padi - Winda Hasma; Damanhuri (Fakultas Pertanian Universitas Majalengka, 2023)
Soil productivity that declines due to the continuous use of inorganic fertilizers for a long period of time has an impact on decreasing the production of rice produced. The need to use organic fertilizers such as liquid organic fertilizer made from lemuru fish to balance soil properties. This study aimed to determine the combination of the use of lemuru fish LOF and NPK fertilizer in rice plant cultivation. The experiment was conducted using a non-factorial complete randomized design with the addition of lemuru fish LOF concentrations as a treatment consisting of 0 ml/l water (P0), 30 ml/l water (P1), 40 ml/l water (P2), 50 ml/l water (P3), and 60 ml/l water (P4). The results showed that the addition of POC lemuru fish with a concentration of 0 ml/l of water gave the best results on all observation variables, namely the number of the productive tiller (21.47), panicle length (21.40 cm), the number of grain per panicle (130.40 grains), the weight of dry rice fields (56.08 g), and the weight of filled grain (4.68 g). It can be concluded that the low nutrient content and little frequency of application were suspected to cause a significant increase in rice crop production.